(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Based on the history of development of the Personalized System of Instruction (PSI) and of Open and Massive Online Courses (MOOCs), this work presents the defining and guiding practices of the PSI and MOOCs and highlights contexts in which PSI and its precursors were applied in a computer-mediated way and the importance of these applications for the development of Distance Education. MOOCs are defined as courses characterized by being unrestricted in terms of the number of learners, having no entry restrictions, such as fees or certificate requirements, and being developed entirely in an online environment, while the PSI is a teaching technology whose practices are: self-pacing in carrying out activities, interdependent teaching units, mastery requirement over the repertoire taught, lectures as a vehicle of motivation, emphasis on the written word, proctor system, practical assessments and objectives based on specific social demands. In our analysis, we found that the history of development of the PSI and the MOOCs bring them closer and farther apart at different times, but that, in addition to being possible, a combination of these practices can be beneficial to both, as long as some precautions are taken.